The Language Policy of the Denikin Regime in Large Cities of Ukraine - Потоцький, В'ячеслав (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
This article deals with the problem of conducting a language policy by the White Guard regime of General Denikin in large cities of Ukraine. Particular attention is paid to the status of the Ukrainian language and its dissemination in such sectors as public education, mass media, theatrical art and advertising. On the example of Kyiv, Kharkiv, Odesa and Poltava, the difference between the declarations of the government and their implementation was analyzed. It is established that under the conditions of the Denikin regime the Ukrainian language was quite legally used in the public space. There is no reason to speak about its complete prohibition at that time.